Kedudukan Hukum Dalam Menjawab “Hilangnya Rasa Aman Dan Hak Konstitusional Terhadap Pejabat Negara Pada Chaos Agustus” - Mangar, Irma; Shinta Azzahra Sudrajat (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2026)
Constitutionally, state officials have the right to work in an environment free from threats, violence, or pressure that could affect their independence. This constitutional right includes not only protection of physical safety, but also protection of freedom of decision-making, carrying out government duties, and accessing state facilities without barriers. When the August Chaos occurred, various forms of disturbance, whether in the form of uncontrolled crowds, anarchic actions, or public disinformation, had the potential to damage the situation and create an unsafe work environment for state officials. The loss of security in state officials has a direct impact on the disruption of the wheels of government. This research is normative research Normative law research has a tendency to image law as a prescriptive discipline where only looking at law from the perspective of its norms which of course is descriptive, this research is carried out in real conditions with the aim of being able to find existing facts to be used as data fillers in this research so that later the point of solving the problem will also be found. One of the most turbulent periods in Indonesia's constitutional dynamics was the